EVIDENCE OF MAMLUK TREASON DURING THE BRITISH CAMPAIGN (1807) IN LIGHT OF THE ENGLISH DOCUMENTS: AN ANALYTICAL STUDY - Mahmoud Ahmed Darwish (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2025)
The historical documents confirmed that Rosetta fell prey to the betrayal of the Mamluk leaders and the complicity of Mohamed Ali and his forces from the Albanians and the conspiring of the Ottomans, in addition to arrogance, arrogance, and British colonial ambitions, the goal of occupying the city was to enable all parties to control the frontiers, including tightening control over the government, even under the British flag. The research deals the letters between the Mamluks and the leaders of the campaign (February 2, 1807 - July 14, 1807),